2017
DOI: 10.1097/mpg.0000000000001492
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Issues and Complications Associated With Inflammatory Bowel Disease

Abstract: Hepatobiliary disorders are common in patients with inflammatory bowel disease (IBD), and persistent abnormal liver function tests are found in approximately 20% to 30% of individuals with IBD. In most cases, the cause of these elevations will fall into 1 of 3 main categories. They can be as a result of extraintestinal manifestations of the disease process, related to medication toxicity, or the result of an underlying primary hepatic disorder unrelated to IBD. This latter possibility is beyond the scope of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 190 publications
1
27
0
2
Order By: Relevance
“…Furthermore, immunosuppression can lead to a reactivation of hepatitis B 101 or cause hepatitis mediated by other viruses, such as cytomegalovirus, Epstein-Barr virus, and others. [102][103][104][105] The prevalence of true hepatic EIMs is reported to be low (<1%). The discrimination from treatment adverse effects usually is difficult.…”
Section: Hepatobiliary Extraintestinal Manifestations In Inflammatory Bowel Diseasementioning
confidence: 99%
“…Furthermore, immunosuppression can lead to a reactivation of hepatitis B 101 or cause hepatitis mediated by other viruses, such as cytomegalovirus, Epstein-Barr virus, and others. [102][103][104][105] The prevalence of true hepatic EIMs is reported to be low (<1%). The discrimination from treatment adverse effects usually is difficult.…”
Section: Hepatobiliary Extraintestinal Manifestations In Inflammatory Bowel Diseasementioning
confidence: 99%
“…However, there is a lack of studies assessing the effects of such treatment in children. According to recommendations, all children infected with HCV who receive anti-TNF agents should have regular evaluation of liver enzymes and viral copies (HCV RNA) [39].…”
Section: Viral Hepatitismentioning
confidence: 99%
“…In a population‐based study, PSC‐AIH overlap was identified in 1.5% of children with IBD, 2.3% in patients with UC, and 0.9% in patients with CD 12 . Elevations in transaminases can occur after an IBD exacerbation, and progression of the biliary disease may be associated with intestinal inflammation 13 . Although PSC‐AIH can respond to the same therapies used in AIH, the prognosis tends to be worse because of progression of biliary disease.…”
Section: Pscmentioning
confidence: 99%